2013
DOI: 10.1080/09603123.2012.678002
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in environmental health impact assessment: Quantitative methods and perspectives

Abstract: Environmental health impact assessment models are subjected to great uncertainty due to the complex associations between environmental exposures and health. Quantifying the impact of uncertainty is important if the models are used to support health policy decisions. We conducted a systematic review to identify and appraise current methods used to quantify the uncertainty in environmental health impact assessment. In the 19 studies meeting the inclusion criteria, several methods were identified. These were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…However, before our study, only Mesa-Frias et al (2013) aimed to conduct a systematic review that identified and appraised current methods for quantifying the uncertainty in environmental health assessment. They found, nevertheless, a much lower number of papers as compared to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before our study, only Mesa-Frias et al (2013) aimed to conduct a systematic review that identified and appraised current methods for quantifying the uncertainty in environmental health assessment. They found, nevertheless, a much lower number of papers as compared to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, none of them were systematic, in terms of using an identifiable database, relevant research words, and explicit criteria for selecting and analyzing the papers included. Only Mesa-Frias et al (2013) aimed to conduct a systematic review that identified and appraised current 2 L. Maxim methods for quantifying the uncertainty in environmental health assessment. Yet, the number of papers assessed was quite low (from three databases they identified 18, 243, and 49 papers, although overlap between them and the period covered were not addressed; 19 papers were selected).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to many other developing cities, PM 2.5 is generated mainly through transportation systems [43,44] which contribute to an increase in permissible level of Air Quality Index [45][46][47]. Recent studies reveal that even normal concentration of PM 2.5 is far more harmful than the commonly known pollutants, such as SO 2 and CO [48]. Studies and epidemiological evidence concerning the effect of PM 2.5 on health are more extensive than studies made on other pollutants [49,50].…”
Section: Transportation and Air Pollution In The City Of Isfahanmentioning
confidence: 99%
“…The city of Isfahan, located in the center of Iran with population of about two million and an urban area of 200 km 2 , is one of the most polluted metropolises. The adverse environmental and health outcomes caused by air pollution have experienced a growing trend.…”
Section: Transportation and Air Pollution In The City Of Isfahanmentioning
confidence: 99%
See 1 more Smart Citation